Perceptions of social workers in Ekurhuleni regarding reunification and de-institutionalisation services rendered by Hope and Homes for Children South Africa - Dolo, Mathabo (My University, 2023)
The negative effects of institutionalization on children’s wellbeing and psychological adjustment have been extensively explored throughout the world, particularly in developing countries. Many children in residential childcare institutions, also known as orphanages, experience various challenges. Institutionalisation affects the children’s psychological adjustment. Hope and Homes for Children South Africa is the leading catalyst in ensuring that children are not harmed in institutions but that they grow up in families. Thus, the goal of this research was to explore the perceptions of social workers in Ekurhuleni regarding reunification and de-institutionalisation services rendered by Hope and Homes for Children South Africa. It is against this background that the present study was conducted. A qualitative research approach, and an exploratory research design was employed as the method of collecting data throughout the study. Fifteen social workers within Ekurhuleni were interviewed. The findings reported positive experiences and perceptions regarding the reunification and de-institutionalisation services rendered by Hope and Homes for Children South Africa. The researcher concluded that the support and services rendered by Hope and Homes for Children South Africa is both sufficient and effective and recommended that the organisation continue offering their services to the various partners
Thesis (M. A. (Social Work)) -- University of Limpopo, 2023
Keywords: Institutionalisation; Child welbeing; Psychological adjustment; Childcare institutions; Child care services -- South Africa -- Gauteng; Child welfare workers; Social workers -- South Africa -- Gauteng; Children -- Institutional care -- South Africa -- Gauteng